2004
DOI: 10.1016/j.ejvs.2004.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Levels, Haemostatic Risk Factors and Patency Rates after Endovascular Treatment of the Above-Knee Femoro-Popliteal Artery

Abstract: Early restenosis or reocclusion after endovascular intervention of lesions in the above-knee femoro-popliteal artery was more frequent following treatment of occlusion (versus stenosis), for patients with diabetes, patients with elevated D-dimer and those without antithrombotic therapy after the procedure. Plasma homocysteine did not appear to influence the outcome of endovascular intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…A study of 68 individuals subjected to vascular and endovascular surgery suggested that fibrinogen levels did not differ significantly (p = 0.510) between the stenosis (n = 23) and non-stenosis groups (n = 45) [6]. This finding was confirmed in another study in which 103 patients were treated with either subintimal angioplasty or intraluminal percutaneous transluminal angioplasty [56]. Multivariate analysis showed no significant correlation between plasma fibrinogen and patency rates [57].…”
Section: Emerging Risk Factorsmentioning
confidence: 68%
See 4 more Smart Citations
“…A study of 68 individuals subjected to vascular and endovascular surgery suggested that fibrinogen levels did not differ significantly (p = 0.510) between the stenosis (n = 23) and non-stenosis groups (n = 45) [6]. This finding was confirmed in another study in which 103 patients were treated with either subintimal angioplasty or intraluminal percutaneous transluminal angioplasty [56]. Multivariate analysis showed no significant correlation between plasma fibrinogen and patency rates [57].…”
Section: Emerging Risk Factorsmentioning
confidence: 68%
“…In contrast, a study of 81 cases treated with percutaneous transluminal angioplasty could not reproduce this finding [73]. Another study including 103 patients treated with subintimal angioplasty or intraluminal percutaneous transluminal angioplasty showed no association between homocysteine levels and the development of reocclusion or restenosis [56]. However, patients with critical ischaemia had significantly higher values of homocysteine than patients with intermittent claudication [56].…”
Section: Homocysteinementioning
confidence: 84%
See 3 more Smart Citations